2021
DOI: 10.3390/life11050394
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Unicompartmental Cartilage Defects of the Knee with Unicompartmental Knee Arthroplasty, Patellofemoral Partial Knee Arthroplasty or Focal Resurfacing

Abstract: Focal chondral defects are common lesions of the articular cartilage. They are predominantly found on the medial femoral condyle and often progress to osteoarthritis of the knee. Various conservative treatment options are available. The conservative treatment might reduce pain and delay the progress of degenerative processes. However, restoration of the articular cartilage cannot be accomplished. If the conservative treatment fails unicompartmental arthroplasty, patellofemoral joint replacement or focal resurf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 90 publications
(106 reference statements)
0
3
0
Order By: Relevance
“…Focal femoral resurfacing of these lesions with mini‐implants has been shown to be a valid alternative. Whilst conventional joint arthroplasty is usually reserved for patients with bone on bone disease, the use of mini‐implants has been mainly advocated as a bridging interim procedure between biological treatments and conventional arthroplasty [4, 6, 10, 28]. In the published literature, these mini‐implants are represented by the HemiCAP ® and UniCAP ® (Anika Therapeutics, Bedford, MA, USA), the Episealer ® (Episealer, Episurf AB, Stockholm, Sweden) and the BioPoly ® (BioPoly, Fort Wayne, IN, USA).…”
Section: Introductionmentioning
confidence: 99%
“…Focal femoral resurfacing of these lesions with mini‐implants has been shown to be a valid alternative. Whilst conventional joint arthroplasty is usually reserved for patients with bone on bone disease, the use of mini‐implants has been mainly advocated as a bridging interim procedure between biological treatments and conventional arthroplasty [4, 6, 10, 28]. In the published literature, these mini‐implants are represented by the HemiCAP ® and UniCAP ® (Anika Therapeutics, Bedford, MA, USA), the Episealer ® (Episealer, Episurf AB, Stockholm, Sweden) and the BioPoly ® (BioPoly, Fort Wayne, IN, USA).…”
Section: Introductionmentioning
confidence: 99%
“…However, after TKA, there is still a quite proportion of unsatisfied patients, which is reportedly related to the indication 5 . Previous studies suggested that most patients with knee osteoarthritis have predominantly unicompartmental medial lesions, which may make them more suitable for unicompartmental knee arthroplasty (UKA) rather than TKA 6 . Furthermore, the indications and contraindications for UKA surgery are changing as UKA surgical techniques continuing to improve and a deeper understanding of Oxford UKA emerges 7 .…”
Section: Introductionmentioning
confidence: 99%
“… 5 Previous studies suggested that most patients with knee osteoarthritis have predominantly unicompartmental medial lesions, which may make them more suitable for unicompartmental knee arthroplasty (UKA) rather than TKA. 6 Furthermore, the indications and contraindications for UKA surgery are changing as UKA surgical techniques continuing to improve and a deeper understanding of Oxford UKA emerges. 7 The changes in indications and contraindications are listed in Table 1 .…”
Section: Introductionmentioning
confidence: 99%